2009
DOI: 10.1038/sc.2009.160
|View full text |Cite
|
Sign up to set email alerts
|

Acute management of traumatic spinal cord injury in a Greek and a Swedish region: a prospective, population-based study

Abstract: Study design: Prospective, population-based study. This paper is part of the Stockholm Thessaloniki Acute Traumatic Spinal Cord Injury Study (STATSCIS). Objectives: To characterize patient populations and to compare acute management after traumatic spinal cord injury (TSCI). Settings: The Greater Thessaloniki region in Greece and the Greater Stockholm region in Sweden. Methods: Inception cohorts with acute TSCI that were hospitalized during the study period, that is September 2006 to October 2007, were identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
2
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 16 publications
0
15
2
1
Order By: Relevance
“…15 Today, in our centre, most patients with acute TSCI undergo surgery early after injury, with the aim of decompressing the spinal cord and/or stabilising the unstable vertebral column. Divanoglou et al 15,16 found in their study that, in Thessaloniki area in Greece, 63 out of 81 cases (78%) were surgically treated for their vertebral lesion after an average time of 10 days, whereas in Stockholm 46 out of 47 (98%) underwent surgery after an average time of 3 days. A surgical stabilisation of the spine may mostly allow the rehabilitation to start earlier and might reduce the risk of complications due to the prolonged forced immobilisation in bed during the acute rehabilitation phase.…”
Section: Introductionmentioning
confidence: 99%
“…15 Today, in our centre, most patients with acute TSCI undergo surgery early after injury, with the aim of decompressing the spinal cord and/or stabilising the unstable vertebral column. Divanoglou et al 15,16 found in their study that, in Thessaloniki area in Greece, 63 out of 81 cases (78%) were surgically treated for their vertebral lesion after an average time of 10 days, whereas in Stockholm 46 out of 47 (98%) underwent surgery after an average time of 3 days. A surgical stabilisation of the spine may mostly allow the rehabilitation to start earlier and might reduce the risk of complications due to the prolonged forced immobilisation in bed during the acute rehabilitation phase.…”
Section: Introductionmentioning
confidence: 99%
“…9 By contrast, the low incidence of deep venous thrombosis and pulmonary embolism in both regions likely reflects the implemented clinical protocol of systematic administration of anticoagulant prophylaxis. 8 Symptomatic UTIs and pneumonia affected similar proportions between regions. Although some complications become self-evident, some others become evident only in the long term, or in the course of comprehensive monitoring.…”
Section: Associated Conditions and Medical Complicationsmentioning
confidence: 95%
“…Details on data collection have been provided elsewhere. 8 Functional outcome was assessed with the 'motor part' of FIM, while the communication and the social cognition parts were disregarded. The motor part of FIM is an ordinal scale with values between 13 and 91, in which the higher the score, the more independent the person is on performing Activities of Daily Living.…”
Section: Data Collection and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…In Stockholm, Sweden, there is an established SCI care program consisting of one hospital-based Spinal Injury Unit, two inpatient rehabilitation centers and one outpatient clinic for lifelong follow-up. In a series of recent articles Divanoglou et al [16][17][18][19] have compared outcomes after traumatic SCI in Sweden to the more fragmented system in Greece. The Swedish group noted improved survival, decreased length of stay and earlier surgical intervention with fewer readmissions compared with the Greek group.…”
Section: Discussionmentioning
confidence: 99%